Program pertukaran jarum dan picagari (NSEP): Cabaran mengurangkan tingkahlaku berisiko pengguna dadah secara suntikan (IDU) - Norulhuda Sarnon,; Ismail Baba,; Zulkarnaian A. Hatta, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
The Needle and Syringe Exchange Programs (NSEP) has been implemented since 2006 to prevent the spread of HIV/AIDS among injection drug users (IDU) in Malaysia. Although its existence has reduced the IDU risk practices, but there are still several challenges faced by the IDU to maintain safe behavior. This qualitative study aims to identify challenges faced by IDU who received NSEP service at IKHLAS drop in centre located in Lorong Haji Taib, Kuala Lumpur. In-depth interviews using semi structured questions were conducted on 13 respondents with convenient sampling approach from Jun 2007. Study found that the challenges mentioned by the respondents to reduce risky behavior are (1) difficulty in facing withdrawal syndromes, (2) difficulty in carrying injecting equipments, (3) influences of social member of the IDU, (4) IDUs’ attitude and (4) reluctance of using condoms. This study suggests more referrals for IDU to Methadone replacement therapy program as well as better case management to meet the actual needs of IDU in order to practice safe behavior